2022
DOI: 10.1111/ijsa.12412
|View full text |Cite
|
Sign up to set email alerts
|

Better explaining the benefits why AI? Analyzing the impact of explaining the benefits of AI‐supported selection on applicant responses

Abstract: Despite the increasing popularity of AI‐supported selection tools, knowledge about the actions that can be taken by organizations to increase AI acceptance is still in its infancy, even though multiple studies point out that applicants react negatively to the implementation of AI‐supported selection tools. Therefore, this study investigates ways to alter applicant reactions to AI‐supported selection. Using a scenario‐based between‐subject design with participants from the working population (N = 200), we varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Recent research showed that algorithm-driven hiring processes are perceived as less fair compared to human-only decisions by candidates ( Lavanchy et al, 2023 ) and that people feel less capable of influencing the outcome of an algorithm compared to human judgment ( Li et al, 2021 ; Hilliard et al, 2022 ). Interestingly, fairness mediates the association between an algorithm-based selection process and organizational attractiveness and the intention to further proceed with the selection process ( Köchling and Wehner, 2022 ). Consequently, it is in the best interest of employers to utilize personality-based algorithms, due to their increased fairness, to improve their attractiveness among potential candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that algorithm-driven hiring processes are perceived as less fair compared to human-only decisions by candidates ( Lavanchy et al, 2023 ) and that people feel less capable of influencing the outcome of an algorithm compared to human judgment ( Li et al, 2021 ; Hilliard et al, 2022 ). Interestingly, fairness mediates the association between an algorithm-based selection process and organizational attractiveness and the intention to further proceed with the selection process ( Köchling and Wehner, 2022 ). Consequently, it is in the best interest of employers to utilize personality-based algorithms, due to their increased fairness, to improve their attractiveness among potential candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Otting and Maier, 2018;Tambe et al, 2019). This effect manifests in employees' feelings of inequality, perceived unfairness, skepticism toward organizational intentions, doubts about the appropriateness of AI-enabled HRM, reluctance to accept AI recommendations and heightened anxiety (K€ ochling and Wehner, 2023;Robert et al, 2020).…”
Section: Risk For Ai Algorithmic Opacitymentioning
confidence: 99%
“…In a similar vein, Köchling and Wehner (2022) investigate ways to improve reactions toward AI-supported selection systems by another important stakeholder in personnel selection: applicants. In their study, they presented participants with either an AI-based selection without any information, with written information, or with video information.…”
Section: Technologymentioning
confidence: 99%
“…The fifth study compares trust, trustworthiness, and trusting behavior for different types of decision‐support (automated, human, and hybrid) across two assessment contexts (personnel selection and bonus payments) and examines trust violations (Kares et al, 2023). The sixth study investigates ways to alter applicant reactions to AI‐supported selection processes (Köchling & Wehner, 2022). Two common topics that emerge across the abstracts are (1) the need to avoid or mitigate negative stereotypes in personnel selection and (2) the use of technology, including machine learning and automation, to improve selection processes.”…”
Section: Summary Of the Papers Included In The Special Issuementioning
confidence: 99%
See 1 more Smart Citation